Chromatin profiling for everyone: FFPE-CUTAC for the theory and practice of modern molecular biology - Xu, Yiling; Henikoff, Steven; Ahmad, Kami (Frontiers in Epigenetics and Epigenomics, 2026)
In 2025, together with the Fred Hutch Summer Undergraduate Research and Summer High School Internship programs, we developed and implemented a laboratory genomics research experience to introduce students to modern molecular biology techniques and bioinformatics. The course centered around using a new method we had developed in 2023 that uses readily available fixed tissue sections on glass slides. Students performed a series of steps to tagment genomic locations of RNA Polymerase II and then used PCR to enrich libraries for next-generation sequencing in a core facility. Students then visualized their data in genomic browser tracks and assessed the results. At the end of the summer, students prepared and presented their work and experiences in seminar format to their cohorts. Overall, the technical simplicity of on-slide chromatin profiling introduced the students to laboratory practice and current techniques in genomics, bioinformatics, and medical sciences.